A formação do professor que ensina matemática nos anos iniciais : uma análise dos conhecimentos legitimados pelo MEC e sua operacionalização na prática - Matos, Diego de Vargas (2017)
This study aims to analyze the knowledge of the teacher who teaches Mathematics in the initial years of Elementary Education legitimized by the evaluation devices elaborated by the MEC and how they are operationalized in practice. The research participants were ten teachers who taught Mathematics in the initial years and who have training, in higher level, in Pedagogy courses, randomly selected in public schools of the city of Porto Alegre of the State of Rio Grande do Sul - RS. As data collection instruments, a questionnaire answered by the teachers and documents was used, in particular: National Curricular Guidelines of the Degree courses in Pedagogy; Guidelines and questions of the National Examination of Student Performance (ENADE) of Pedagogy courses; Matrix of Reference and Mathematics questions of the Brazil Test of the 5th year. The answers given by the teachers were analyzed qualitatively through the Discursive Textual Analysis method, relating them to the guidelines, descriptors and exam questions. The theoretical contributions that served as basis for this research were authors as Tardif (2002), Shulman (1986; 2014), Perrenoud (1999a; 1999b; 2000), Freire (1996), Saviani (2009), Fiorentini (1995), Nacarato, Mengali e Passos (2011), among others. The analysis was mainly based on the results of Shulman's (1986) studies on the categorization of teacher knowledge. The analysis of the data came from three categories a priori, be they: knowledge of the content; Pedagogical knowledge of content; curricular knowledge. From these categories it was possible to delineate the analysis of the collected data, emerging, thus, subcategories. It is possible to affirm that the knowledge of the teacher who teaches Mathematics in the initial years legitimized by the evaluation devices elaborated by the MEC is, in fact, knowledge of content, pedagogical knowledge of content and curricular knowledge, being the last two more evidenced during the analysis. In addition, it concludes that the majority of the participating teachers of the research operationalize their practice with more emphasis and concern in the knowledge of content, affirming to modify, during their teaching practice, their pedagogical knowledge and curricular knowledge acquired in the course of Pedagogy.